2020
DOI: 10.4103/jmu.jmu_108_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of transrectal ultrasound elastography in the diagnosis of prostate carcinoma

Abstract: Background: The purpose of this study was to evaluate the diagnostic value of transrectal real- time strain elastography (RTE) in identifying prostatic carcinoma (PCa). Methods: 60 patients suspected of having PCa based on abnormal digital rectal examination and raised prostate specific antigen levels underwent transrectal ultrasound (TRUS), color Doppler (CD) and RTE. Elastograms were scored on a five point scale based on distribution of strain in relation to hypoechoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Benign lesions had lower elastography scores, whereas malignant lesions had higher scores. These findings align with those of Kanagaraju et al 18 , who reported similar results in their study. This correlation can be attributed to the fact that malignant lesions are characterized by replacing glandular tissue with malignant cells, resulting in a higher stiffness than benign lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Benign lesions had lower elastography scores, whereas malignant lesions had higher scores. These findings align with those of Kanagaraju et al 18 , who reported similar results in their study. This correlation can be attributed to the fact that malignant lesions are characterized by replacing glandular tissue with malignant cells, resulting in a higher stiffness than benign lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Final reports were issued after reaching an agreement. 15,16 Radical surgery and follow-up for PCa: The patients received general anesthesia. Dissociation was performed in the retrorectal space to expose the prostate apex, prevesical space, and etropubic space.…”
Section: Methodsmentioning
confidence: 99%
“…The important aspect from human literature to be considered to implement sonoelastography in canine prostate evaluation is that both SE and 2D‐SWE have been proven to be highly sensitive not only to distinguish the healthy from diseased parenchyma but also to guide tissues biopsies, thus reducing the need for a systematic prostate sample and improve the accuracy of diagnosis, distinguish the lesions to be sampled with suspicion of malignancy from more benign lesions (Anbarasan et al, 2021; Kanagaraju et al, 2020; Secasan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%